Pediatric mediastinal lymphatic malformation: misdiagnosis analysis and literature review - Wen Zhao; Siqi Zhang; Xinxin Qi; Songyu Teng; Longwei Sun; Hongwu Zeng (BMC, 2024)
Abstract Objectives Mediastinal cystic lymphatic malformation (MCLM) in children is prone to misdiagnosis as cystic teratoma. We compared the clinical and radiologic features between the two diseases and performed a cross-comparison with previous research on adult cases. This study aims to identify characteristic pediatric manifestations to improve diagnostic accuracy. Methods A retrospective study of clinical and radiologic data was conducted on 12 MCLM and 20 cases of cystic teratomas confirmed by pathology or intervention biopsy. Clinical characters and radiology features (mass location and morphology, density, component, secondary complication) were recorded and compared. We reviewed clinical studies on MCLM published in the past decades, analyzing radiological differences and comparing pediatric MCLM cases at our hospital with those in the literature. Results Group comparison in pediatrics between MCLM and cystic teratomas: There were significant age differences (p = 0.036), shape (p = 0.003), CT difference value (p < 0.001), CT difference ratio (p < 0.001), calcification (p < 0.001), fat (p < 0.001), and typing (p < 0.001) between the two diseases. An analysis of literature data on MCLM cases involved 16 studies. Conclusion The absence of internal fat or irregular morphology, along with a minimal CT difference value, may suggest the diagnosis of MCLM. In pediatric cases, anterior mediastinal diseases tend to extend toward the neck, and the presence of the thymus can complicate the component analysis, thereby increasing the risk of misdiagnosis. Clinical diagnosis and differential diagnosis of pediatric MCLM rely heavily on imaging evaluation.